Patients' satisfaction: A study of specialist clinic Queen Elizabeth Hospital Kota Kinabalu Sabah - Pius Jauni, @ Pious (2011)
Introduction The patients’ or customers’ satisfaction has been the main issues in any service industry particularly in the healthcare organization. The healthcare organizations operating in the public sectors such as hospital are experiencing low quality of services leading to dissatisfaction among the users of healthcare. Purpose of the study The purpose of the study is to assess the satisfaction of patients who have patronized or visited at the specialist clinic provided by the government hospital and to identify factors leads to patient’s satisfaction. Methodology The cross-sectional approach was used in this study to assess patients’ satisfaction in the Specialist Clinic of the Queen Elizabeth Hospital Kota Kinabalu. The SERVQUAL or Service Quality Instruments was used as a tool to measure the customers’ services provided at this hospital. The sample of sixty (n=60) respondents was selected randomly in ﬁve (5) chosen clinics. The data collection was conducted for two weeks. Finding The analysis revealed that although the majority of the respondents were satisﬁed with services provided but their level of satisfaction was not correlated with the respondent's expectation on the service quality. Most of them expected the specialist clinic to provide service at the time promised to satisfy their level of satisfaction and the clinic to be visually appealing or better environment as found in the SERVQUAL dimension. The perception ﬁnding had put Empathy to be positively and signiﬁcantly correlated in their level of satisfaction. On the Gap analysis found that all the perception dimensions were higher than the expectations. The high positive gap score of 4.65 was on Empathy. This revealed that staff of the specialist clinic must be more understanding on the parts of patients’ illness. The other factors highlighted on their dissatisfaction on the service provided were long waiting, congested, many patients and poor communication between the staff and patients. Conclusion Thus, this study sheds light on many ﬁelds for improvement by the healthcare management. Emphasis should put more on the cause of dissatisfaction as revealed in the ﬁnding. This ﬁnding has also provided the hospital management or managers the directions to develop strategies which will meet the patients’ expectation of service quality to restore their trust, conﬁdence and satisfaction in the government hospital.